Need Analysis for the Development of Learning Video Based on Explaindio in Physics Lesson of Senior High School to Improve Learning Outcomes During the Covid-19 Pandemic - Nurliana, Nurliana; Zulirfan, Zulirfan; Fakhruddin, Fakhruddin (Journal of Educational Sciences, 2021)
During the Covid-19 pandemic, learning is no longer undertaken offline (outside the network) but online (in the network). This condition demands the informative and communicative media for learning activities. One of the media that can be directly interacting with students is learning video. The teacher needs to conduct a needs analysis to ensure the use of learning videos, especially those based on Explaindio. The research was conducted in a correlational quantitative approach. The action research was undertaken at SMA Negeri 4 Pekanbaru with a sample of 36 students. The data collected from the questionnaire consisted of 10 items. Data analysis by substituting respondents’ results through descriptive statistics, Product Moment correlation, and t-test. The results of the analysis indicated that the importance of utilizing meaningful videos to meet the learning needs of students. Learning videos based on Explaindio provide space for teachers to design videos in accordance with their needs. Complete and communicative learning videos can provide meaningful information and experiences to students so that they have a positive impact on student learning progress.